Nutrition Education in Mexican Elementary School Communities Experienced in Social Participation in Health - Hernández Ramírez, José Cutberto (2023)
As the main objective, this work seeks to analyze the nutrition knowledge of educators and their teaching practices for such topic (EAN in its Spanish acronym) in four school communities experienced in Social Participation in Health located in the central region of Mexico. Thus, it will be possible to outline their capabilities. Regarding the methodology, it consists of a comparative case. In addition, to discover the general nutrition knowledge of teachers (n=43), the researchers adapted and applied an international standardized questionnaire. Therefore, in each school, a virtual symposium was organized where educators presented their teaching practice strategies in EAN. Subsequently, the information was processed through the ethnographic tools of the PROVERIFICA labor process analysis model around the following three questions in terms of planning, implementation, and evaluation in teaching practice: 1) what is done?, 2) with what it does? and 3) how is it done? Regarding the results, the average percentage of correct answers in the general nutrition knowledge questionnaire in the four schools was 61 ± 18.9. R. Moreover, in two schools predominates a teaching practice approach based on cognitive objectives, and in the others predominates an active education approach aimed at cognitive and emotional development through praxis and home-school recursion. Therefore, the researchers conclude that the pedagogical approach required to improve the eating habits of students; requires to go beyond cognitive aspects, to implement strategies aimed at promoting attitudes. Therefore, the researchers conclude that the impact on students' eating habits requires a pedagogical approach that not only transcends cognitive aspects, but also implements strategies aimed at promoting attitudes. In addition, the active education models practiced in two of the schools studied need legal reinforcement so that the State assumes its constitutional obligation to support them, instead of delegating the responsibility of ensuring the effective exercise of the right to education.